2019
DOI: 10.1111/ajpy.12246
|View full text |Cite
|
Sign up to set email alerts
|

An umbrella review of the evidence for equine‐assisted interventions

Abstract: Objective: To establish the evidence base for animal-assisted interventions, and specifically, hippotherapy and other interventions involving horses, in the context of improving biological, physical, psychological and social functioning, and outcomes in humans. Method: A review of systematic reviews (an umbrella review) was carried out using a modified Joanna Briggs Institute methodology and following PRISMA guidelines. Inclusion criteria were any interventions that included a live horse, for humans of any age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 43 publications
2
28
0
4
Order By: Relevance
“…An umbrella review of equine-assisted interventions was published early in 2019 [30], which included any interventions that involved a live horse, for humans of any age, and for any therapeutic purpose. This review suggested that the evidence underpinning equine-assisted interventions was equivocal, and as such, it cannot be recommended as a best practice.…”
Section: Introductionmentioning
confidence: 99%
“…An umbrella review of equine-assisted interventions was published early in 2019 [30], which included any interventions that involved a live horse, for humans of any age, and for any therapeutic purpose. This review suggested that the evidence underpinning equine-assisted interventions was equivocal, and as such, it cannot be recommended as a best practice.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the potential benefits of equine assisted psychotherapy and counselling have been studied as well, even if potential positive results [118] emerged along with negative ones [119]. The most comprehensive work analyzing the application of equine assisted interventions has been recently published by Stern and Chus-Hensen [120], considering both adults and children treatments across different conditions.…”
Section: Horses In Equine Assisted Interventions (Eais)mentioning
confidence: 99%
“…Os benefícios da equoterapia sobre a qualidade foram evidenciados em uma recente umbrela review, que é uma revisão de revisões de literatura (STERN; CHUR-HANSEN, 2019). O fato do domínio meio ambiente ter sido o único a apresentar aumento significativo dentre os demais é interessante devido ao idoso avaliado ser institucionalizado.…”
Section: (Muitíssimo)unclassified